Burial Traditions of Toraja: Reflections of Megalithic Belief and Social Stratification - Rosmawati Rosmawati (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study explores the symbolic meanings of Toraja mortuary practices and their relationship to belief systems and social hierarchy. Drawing on ethnographic methods—participant observation of funeral ceremonies, semi-structured interviews, oral-tradition documentation, and archival research—the research examines burial forms at the Sillanan site in Tana Toraja, South Sulawesi. The findings reveal that Toraja burials, including Liang Sillik, Liang Erong, Liang Tokek, Liang Pak, and Patane, along with coffin types (erong) shaped as rectangles, buffalo, or boats, reflect a megalithic belief system that emphasizes the powerful influence of ancestral spirits on human welfare. These practices also encode social stratification: lower social groups were interred in simpler caves, while high-ranking nobles used elaborately carved boat- or buffalo-shaped coffins placed in elevated locations. The mortuary system illustrates a worldview in which life and death form a continuous cycle, where the spirit world (puya) mirrors earthly society. For archaeology, the ethnographic data provide an important analog for interpreting material remains, offering insights into the ideological and social frameworks that inform the creation, use, and deposition of artifacts. This research highlights how Toraja burial technology and rituals embody enduring connections between the living and the dead, as well as between belief, social order, and material culture.